Educational Psychology In Developing Students' Emotional Intelligence - Sugiri, Atot; Yudha Kusumawardana, Muhammad (PT ARRUS Intelektual Indonesia, 2025)
Educational psychology plays a crucial role in developing students' emotional intelligence, which includes the ability to recognize, understand, and manage emotions effectively. The background of this study is based on the importance of emotional intelligence in enhancing academic achievement, building healthy social relationships, and supporting students' psychological development. This study aims to analyze the role of educational psychology in fostering students' emotional intelligence through theoretical and empirical approaches. The research employs a qualitative method with a literature review. Data collection techniques involve literature analysis from various relevant sources, while data analysis is conducted using a descriptive-qualitative approach. The results indicate that the application of educational psychology theories, such as emotional development theory and social learning, contributes to the enhancement of students' emotional intelligence. The study findings reveal that educational psychology-based learning strategies, such as experiential learning and self-reflection, can improve emotional regulation skills. The conclusion of this study emphasizes that the effective implementation of educational psychology can foster students' emotional intelligence, positively impacting their emotional well-being and academic performance.